Characterization of food waste-recycling wastewater as biogas feedstock - Shin, Seung Gu; Han, Gyuseong; Lee, Joonyeob; Cho, Kyungjin; Jeon, Eun-Jeong; Lee, Changsoo; Hwang, Seokhwan (Elsevier BV, 2015)
A set of experiments was carried out to characterize food waste- recycling wastewater (FRW) and to investigate annual and seasonal variations in composition, which is related to the process operation in different seasons. Year-round samplings (n = 31) showed that FRW contained high chemical oxygen demand (COD; 148.7 +/- 30.5 g/L) with carbohydrate (15.6%), protein (19.9%), lipid (41.6%), ethanol (14.0%), and volatile fatty acids (VFAs; 4.2%) as major constituents. FRW was partly (62%) solubilized, possibly due to partial fermentation of organics including carbohydrate. Biodegradable portions of carbohydrate and protein were estimated from acidogenesis test by first-order kinetics: 72.9 +/- 4.6% and 37.7 +/- 0.3%, respectively. A maximum of 50% of the initial organics were converted to three major VFAs, which were acetate, propionate, and butyrate. The methane potential was estimated as 0.562 L CH4/g VSfeed, accounting for 90.0% of the theoretical maximum estimated by elemental analysis. (C) 2015 Elsevier Ltd. All rights reserved.